Lexical Features And Translation Of Cultural References In The Chinese Subtitles Of Selected Feature And Animated Feature Films - Zhang, Yadan (2024)
This study addresses a gap in research by delving into corpus-based translation studies, specifically in the chinese context of subtitling. The objective of this study is to explore the lexical features, distribution of cultural references and subtitling strategies of cultural references in translated chinese subtitles from feature films and animated feature films by means of corpora methods. The study analysed comparable corpora of translated chinese subtitles from english feature films and native chinese subtitles, alongside parallel corpora of bilingual subtitles (english and chinese) from both feature films and animated feature films. The lexical features of translated chinese subtitles were examined by using the parameters proposed by pavesi et al. (2015). Furthermore, three specific lexical items, namely, forms of address, model particles and vulgarism summarized by the researcher are also employed to investigate lexical features of translated chinese subtitles. Further, the classification of cultural references and their subtitling strategies are analysed by adopting díaz-cintas and remael (2020) taxonomy of cultural references and model of subtitling strategies. The data were analysed by corpus tools of wordsmith, antconc and uam corpus tool. The major findings of the corpora analysis reveal that translated chinese subtitles exhibit features of lexical simplification in both translated feature films and animated feature films. Further, the investigation of the three specific lexical items reveals native chinese subtitles use more forms of address and modal particles compared to translated chinese subtitles.